Intelligent Computing for Cultural Heritage (Taylor & Francis, 2024)
This book offers a global perspective on the latest advancements and trends in digital humanities and intelligent computing of cultural heritage, covering both academic research and case studies within cultural institutions. This edited volume brings together views and practices from different regions, including Asia, Europe, Africa, North America, and Australia. It offers innovative approaches and case studies related to humanities data and digital methods, with a focus on digital humanities research and pedagogy and cultural heritage organisation and preservation, in particular the development of digital knowledge repositories and methods for digital intelligence in cultural heritage. Each case study highlights unique cultural characteristics and academic histories, resulting in diverse development priorities and thematic directions. However, this diversity can also lead to imbalances and isolation within the field. To gain a better understanding of the complex trends in the development of the digital humanities, this book offers valuable insights from case studies and research practices, showcasing global contributions from scholars and institutions. This title will appeal to scholars and students of digital humanities and information science, particularly those studying heritage management and intelligent computing. Professionals working at the intersection of technology and cultural heritage will also find this book of great interest. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.